2017
DOI: 10.1093/alcalc/agx100
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant Outcomes of Persons Receiving a Liver Graft for Alcoholic Liver Disease

Abstract: In this review, we cover medical and psychosocial outcomes for ALD patients and compare their outcomes to other liver transplant recipients. While alcohol relapse occurs following transplant, the rates of return to heavy alcohol use, especially at amounts that are health harmful, are low at ~20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…However, with comparable outcomes following LT for other etiologies as well as a low rate of graft failure following recidivism, referrals for ALD patients requiring transplant are anticipated to increase [41–44]. There are a number of potential reasons for an expected increase in the proportion of LTs performed for ALD including a proportional decrease in HCV transplants (with a resultant increase in the proportion of ALD and other non‐HCV etiologies), an improved understanding of the role of LT and patient selection for acute alcoholic hepatitis including the need to obviate the historical six‐month abstinence rule, an evolving understanding of factors influencing recidivism, an increase in HCC in the setting of ALD, and favorable post‐transplant survival relative to other etiologies [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…However, with comparable outcomes following LT for other etiologies as well as a low rate of graft failure following recidivism, referrals for ALD patients requiring transplant are anticipated to increase [41–44]. There are a number of potential reasons for an expected increase in the proportion of LTs performed for ALD including a proportional decrease in HCV transplants (with a resultant increase in the proportion of ALD and other non‐HCV etiologies), an improved understanding of the role of LT and patient selection for acute alcoholic hepatitis including the need to obviate the historical six‐month abstinence rule, an evolving understanding of factors influencing recidivism, an increase in HCC in the setting of ALD, and favorable post‐transplant survival relative to other etiologies [45–47].…”
Section: Discussionmentioning
confidence: 99%
“…3 Some may develop greater coping resources, improve adherence behaviors, or stop abusing substances. 22 Patients may also become more overwhelmed or depressed in the setting of new medical challenges. 23 The period that precedes transplantation can also be highly stressful and thus, may not accurately reflect patients’ baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of post-transplantation alcohol relapse is an issue of concern. Reported post-transplant alcohol relapse rates in recipients with ALD range from 15% to 50% [48][49][50][51] . A prospective study 48 of 167 patients found that 42% of the individuals included in the cohort had taken at least one drink by the end of 4.5 years after transplantation, and 26% had engaged in binge drinking.…”
Section: Post-transplantation Relapse Predictors Of Relapse: Risk Stratificationmentioning
confidence: 99%